Kontribusi Kepemimpinan Kepala Sekolah Dalam Peningkatan Disiplin Kerja Guru Melalui Program Workshop Motivasi Kerja Di Mts Muhammadiyah Surakarta - Triono, Agus, Prof. Dr. Ali Imron Al-Ma'ruf (2017)
The school principal as leader of the governing everything in school, have a very important role for the advancement of education. The purpose of this study was to describe the contribution of principals in improving labor discipline teachers through workshops program in MTS Muhammadiyah Surakarta and to describe forms of discipline teachers who could be improved and that is difficult to increase through the workshop program in MTs Muhammadiyah Surakarta. Sources of data in this study consisted of primary and secondary data sources. Sources of primary data such as text data obtained through interviews and interviews with informants or participants were sampled research, secondary data sources such as data that is already available and can be obtained by investigators by reading, viewing or listening. In collecting the data the researcher used observation / observation, interviews and document analysis. This type of research is qualitative deskriptive. Researchers analyzed this research with data collection., data reduction, data presentation, and drawing conclusions / verification .. This study shows that the contribution made by the principal to the teachers in MTs Muhammadiyah relating to effortnya is to involve teachers in educational workshops. The goal is teachers can improve their discipline is based on a) comply with the rules, values, and laws that apply in school, self-awareness of teachers to obey orders without question, b) affect, change, fostering and shaping behavior in accordance with the values specified or taught, c) educate, train, control and improve the behavior of teachers, d) knowledge, experience and expertise of teachers can work effectively. Some forms of discipline that could be improved with the workshop is 1) discipline in following and obeying rules, values, and laws, 2) time discipline, and discipline in behavior. Keywords: contributions, work discipline-teachers, workshop